Between Mom and Jo a novel - Peters, Julie Anne (Little, Brown, 2006)
Fourteen-year-old Nick has a three-legged dog named Lucky 2, some pet fish, and two mothers, whose relationship complicates his entire life as they face prejudice, work problems, alcoholism, cancer, and finally separation.